P363 Combined oral and topical antibiotic therapy for male partners of women with bacterial vaginosis: a pilot study. (14th July 2019) - Plummer, Erica; Vodstrcil, Lenka; Fairley, Christopher; Danielewski, Jennifer; Murray, Gerald; Doyle, Michelle; Fehler, Glenda; Kaiser, Marti; Mcguinness, Colette; Garland, Suzanne; Bulach, Dieter; Chow, Eric; et al.
Abstract : Background: More than 50% of women experience recurrence of bacterial vaginosis (BV) within 3–6 months following first-line antibiotics. Increasing evidence suggests that reinfection from an untreated sexual partner contributes to BV-recurrence. We conducted a pilot study of combined oral and topical antibiotic treatment of male partners of women being treated for BV. Methods: Women attending Melbourne Sexual Health Centre with symptomatic BV (≥3 Amsel's criteria and Nugent Score[NS]=4–10) were recruited with their regular male partner (RSP). Women received oral metronidazole 400 mg twice daily ( BD ; or 2% clindamycin cream nocte, if contraindicated), for 7-days. Males received oral metronidazole 400 mg BD and 2% clindamycin cream topically to penile skin BD, for 7-days. Couples self-collected genital samples (vaginal swab, penile swab and male urine) and completed questionnaires for 4-weeks post treatment. The proportion of women cured (NS≤7) at 4-weeks post treatment was calculated. A subset of couples will be followed to 12-weeks post treatment and this data will also be available for presentation. Genital samples will be analysed to understand the impact of partner treatment on the genital microbiota, and the contribution of behaviours and host factors to BV-recurrence. Results: Data from 46 couples has been analysed. Thirty-eight women (83%) reported a past history of BV and 14 (30%) reported intra-uterine device (IUD) use. Most RSPs were uncircumcised (n=38, 83%). Treatment adherence was high, with 91% taking ≥70% of prescribed doses. The proportion of women cured at 4-weeks was 93% (n=43/46, 95%CI: 82–99%). All cases of BV-recurrence (n=3) had a past history of BV and an uncircumcised RSP. Two cases had an IUD in situ and one reported condomless vaginal sex during treatment. Conclusion: Treating sexual partners of women with BV may be an effective strategy for improving BV-cure. Randomised controlled trials of partner treatment currently underway will help determine the effectiveness of this intervention. Disclosure: No significant relationships.